The impact of new production technologies on the efficiency of agricultural enterprises - Irina P. Bogomolova, Ekaterina A. Belyaeva,; Zaitseva, Natalia A.; Larionova, Anna A.; Bogomolov, Anton V.; Elena I. Krivenko, Irina N. Vasilenko, (Opción, 2020)
The article discusses the directions that contribute to improving the development efficiency of flour-milling enterprises, taking into account the effectiveness of the product marketing system via general scientific methods and theories of studying socio-economic phenomena and processes: logical, dialectical, systemic, technological, process and situational approaches. It has been shown that the diversification of production is an effective direction for the development of flour milling enterprises. In conclusion, to solve the priority tasks of product quality management in the aspect of ensuring sustainable effective development of the flour-milling industry, it is necessary to improve the equipment and technology of grain processing.